2017
DOI: 10.1002/sej.1275
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the value of real options: How firm‐specific learning conditions affect R&D investments under uncertainty

Abstract: Research Summary Why do some firms increase R&D investments in the face of uncertainty, while others do not? Contrary to common wisdom, this study posits that uncertainty prompts firms to invest in R&D. The value to invest under uncertainty is, however, bounded by a firm's learning conditions (i.e., human capital, relatedness of innovation activities, and industry maturity). An empirical test on a cross‐industry panel of 551 business divisions of manufacturing firms reveals how organization‐environment interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 101 publications
(203 reference statements)
1
40
0
Order By: Relevance
“…In addition, the positive effect of uncertainty on R&D investment is intensified when the competition is fierce and a firm's market power is low. Ross, Fisch, and Varga [10] also shows that the increase in uncertainty stimulates R&D investment, and this relationship is positively moderated by factors that increase corporate learning capacity, such as human capital, scope of innovation activities of firms, and industry maturity. In these studies, the rationale for uncertainty to have a positive impact on R&D investment is the strategic growth option that is inherent in R&D investment.…”
Section: Uncertainty and Randd Investment: A Conflict Between Deferral mentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, the positive effect of uncertainty on R&D investment is intensified when the competition is fierce and a firm's market power is low. Ross, Fisch, and Varga [10] also shows that the increase in uncertainty stimulates R&D investment, and this relationship is positively moderated by factors that increase corporate learning capacity, such as human capital, scope of innovation activities of firms, and industry maturity. In these studies, the rationale for uncertainty to have a positive impact on R&D investment is the strategic growth option that is inherent in R&D investment.…”
Section: Uncertainty and Randd Investment: A Conflict Between Deferral mentioning
confidence: 94%
“…In particular, it has been confirmed that uncertainty increases the positive effect of uncertainty on R&D investment when a firm belongs to the competitive industry or has low market dominance. Ross et al [10] also identified a positive relationship between uncertainty and R&D investment. This relationship is mediated by factors affecting the learning effects that are created by R&D investments, such as corporate human capital and product lineup and industry maturity.…”
Section: Introductionmentioning
confidence: 95%
“…According to the empirical results, there is a significant and positive correlation between EPU and CER, the total effect is 1.176, this indicates that EPU encourages the corporations to fulfill their environmental responsibilities. The direct effect of EPU on CER is 1.122, so the intermediary effect of EPU on CER through the leverage ratio is ϑ 1 × β 2 = (−0.0495) × (−1.105) = 0.054 (9) which is equal to θ 1 minus β 1 . Therefore, EPU induces an increase in the level of CER through the reduction in the leverage ratio.…”
Section: Intermediary Effect Modelmentioning
confidence: 99%
“…With regard to the effect of EPU on innovation, Xu [8] thought that a higher level of EPU impedes innovation not only through the traditional channel of irreversible investment, but also through the channel of cost of capital. In addition, Ross et al [9] and Vo and Le [10] pointed out that, based on the strategic growth choice theory and the real option theory, corporations will increase their investment in research and development (R&D) as well as innovation when faced with a higher level of policy uncertainty. In terms of the effect of EPU on cash holdings, Duong et al [11] and Demir and Ersan [12] found that corporations are willing to hold more cash when the level of EPU rises.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical basis that supports these models and premises is found in modern finance theory, which was initially presented in the works of Modigliani and Miller (1958, 1959, 1963. The recent studies that use alternative assessment methodologies, such as real options, are also noteworthy (Deeney & Cummins, 2019Kozlova, 2017Ross, Fisch, & Varga, 2018;Vernimmen, Quiry, Dallocchio, Le Fur, & Salvi, 2018). These works allowed several questions to be formulated about the influence economic and financial variables had on the market value of companies and their sources of financing.…”
Section: Introductionmentioning
confidence: 99%